Histórico de contaminação por elementos-traços na planície aluvial do Alto Rio Paraná - Remor, Marcelo Bevilacqua (2013)
Objective: Investigate the temporal evolution of the supply of trace elements, identifying trends in the historical concentration of the drainage basin of the Upper Paraná River Floodplain. Material and Methods: The corers extracted of the Patos Pond and the Garças Pond were sliced into uniform intervals of 2.2 and 2.0 cm respectively. Later the geochronological analysis was performed by the method radiochemical of isotope 210Pb. The quantification of element Mercury was performed with the equipment LUMEX. While the others trace elements were quantified by flame atomic absorption spectrometry, opening following the Method USEPA 3050B. Results: The sedimentation rate of the Garças Pond is 7.7 mm year-1 (2.66 kg m-2 year-1) and of the Patos Pond is 6.0 mm year-1 (1.94 kg m-2 year-1). Conclusion: The sediments of the Patos Pond and the Garças Pond have concentrations of trace elements similar to the background. The main factor that regulates the supply of trace elements in the Upper Paraná River Floodplain is the flood pulses, which can be magnified by the El Niño phenomenon. The burning of cane sugar, increased agriculture, urbanization and release of effluents from steel mills contributed to the increase in the concentration of some trace elements. While the adsorption by macrophytes and process oligotrophication caused by damss upstream of the floodplain, resulted in the reduction of the concentration of other elements